PENGARUH GAYA KEPEMIMPINAN DAN REWARD TERHADAP KINERJA KARYAWAN Le POLONIA HOTEL MEDAN - Suryadi Suryadi; Cahyo Pramono; M.Isa Indrawan (Ensiklopedia Education Review, 2021)
This study aims to determine the effect of leadership and reward on the performance of hotel employee at Le Polonia Hotel Medan, both partially and simultaneously. The population and sample in this study were all permanent employees as many as 65 people and all of them were used as respondents using the census method. Data collected through the distribution of questionnaires with a Likert scale then tested the validity and reliability of the questionnaire. The data analysis technique used is the Multiple Linear Regression Analysis method, after passing the classical assumption test using the SPSS program. In this study leadership and reward as independent variables, employee performance as the dependent variable. The results of this study prove that leadership and reward both partially and simultaneously have a positive and significant effect on the performance of the employees of Le Polonia Hotel Medan.Keywords: Leadership, reward and employee performance.